2009
DOI: 10.1038/leu.2009.208
|View full text |Cite
|
Sign up to set email alerts
|

Hsa-mir-125b-2 is highly expressed in childhood ETV6/RUNX1 (TEL/AML1) leukemias and confers survival advantage to growth inhibitory signals independent of p53

Abstract: MicroRNAs (miRNAs) regulate the expression of multiple proteins in a dose dependent manner. We hypothesized that increased expression of miRNAs encoded on chromosome 21 (chr 21) contribute to the leukemogenic role of trisomy 21. The levels of chr 21 miRNAs were quantified by qRT-PCR in four types of childhood ALL characterized by either numerical (trisomy or tetrasomy) or structural abnormalities of chr 21. Suprisingly high expression of the hsa-mir-125b-2 cluster, consisting of three miRNAs, was identified in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
97
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(105 citation statements)
references
References 42 publications
3
97
0
5
Order By: Relevance
“…22 Functional studies showed that inhibition of miR-125b sensitized TEL-AML1-positive cells to doxorubicin. 24 These studies exemplify a role for miR-125b in leukemogenesis and points to miR-125b as potential therapeutic target.…”
Section: Oncogenic Mirnasmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Functional studies showed that inhibition of miR-125b sensitized TEL-AML1-positive cells to doxorubicin. 24 These studies exemplify a role for miR-125b in leukemogenesis and points to miR-125b as potential therapeutic target.…”
Section: Oncogenic Mirnasmentioning
confidence: 99%
“…35 MiR-125b and neighboring miRNA genes let-7c, miR-99a and miR-100 were aberrantly upregulated in TEL-AML1-positive ALL and different myeloid leukemias (Tables 1 and 2). 24,46,47 Pro-B cells gained a survival advantage 24 and differentiation of CD34 þ myeloid progenitors was disturbed upon miR-125b overexpression. 46,47 Moreover, the oncogenic activity of miR-125b was recently shown in mice, which were transplanted with fetal liver cells that overexpressed miR-125b.…”
Section: Oncogenic Mirnasmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 An evolutionally conserved miRNA, miR-125b, has been implicated in human cancers. [7][8][9][10][11][12] MiR-125b-1, mapped on 11q24, has been found to be a target of recurrent chromosomal abnormalities seen in both lymphoid and myeloid malignancies. [7][8][9][10] We previously reported an insertion of miR-125b-1 into the IGH locus in a patient with B-cell precursor acute lymphoblastic leukemia (BCP-ALL).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we show that overexpression of miR-125b is sufficient both to shorten the latency of BCR-ABL-induced leukemia and to independently induce leukemia in a mouse model. M icroRNAs are a family of small noncoding RNA (18)(19)(20)(21)(22)(23)(24)(25) nucleotides) that act as crucial posttranscriptional regulators of genes involved in many fundamental process, including differentiation, proliferation, and apoptosis (1,2).…”
mentioning
confidence: 99%